2021
DOI: 10.3389/fspas.2021.751244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreshock Transients on the Flank Magnetopause and Magnetosphere and the Ionosphere

Abstract: Mesoscale (on the scales of a few minutes and a few RE) magnetosheath and magnetopause perturbations driven by foreshock transients have been observed in the flank magnetotail. In this paper, we present the 3D global hybrid simulation results to show qualitatively the 3D structure of the flank magnetopause distortion caused by foreshock transients and its impacts on the tail magnetosphere and the ionosphere. Foreshock transient perturbations consist of a low-density core and high-density edge(s), thus, after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…An immediately noticeable result is that the HFA appears only south of the equator although the IMF has a north‐south symmetry on both sides of the TD. As the TD propagates tailward, it causes significant pressure perturbations and distortions on the southern magnetopause (C. P. Wang et al., 2021b).…”
Section: Simulation Results: Global Symmetry Breaking Of Hfas and The...mentioning
confidence: 99%
“…An immediately noticeable result is that the HFA appears only south of the equator although the IMF has a north‐south symmetry on both sides of the TD. As the TD propagates tailward, it causes significant pressure perturbations and distortions on the southern magnetopause (C. P. Wang et al., 2021b).…”
Section: Simulation Results: Global Symmetry Breaking Of Hfas and The...mentioning
confidence: 99%
“…Although HFAs and FBs disturb the magnetosphere—ionosphere system and accelerate particles, how they form is still unclear. Simulations (Burgess, 1989; Lin, 2002; Omidi & Sibeck, 2007; Omidi et al., 2010; Thomas et al., 1991; Wang et al., 2021a, 2021b) have shown that they form from interaction between foreshock ions and solar wind discontinuities. In papers using recent MMS observations by Liu, An, et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although HFAs and FBs disturb the magnetosphere-ionosphere system and accelerate particles, how they form is still unclear. Simulations (Burgess, 1989;Lin, 2002;Omidi & Sibeck, 2007;Omidi et al, 2010;Thomas et al, 1991;Wang et al, 2021aWang et al, , 2021b have shown that they form from interaction between foreshock ions and solar wind discontinuities. In papers using recent MMS observations by and PIC simulations by An et al (2020), a kinetic formation model was proposed: as foreshock ions become demagnetized around a discontinuity and electrons remain magnetized, a Hall current forms and varies the magnetic profile.…”
mentioning
confidence: 99%
“…Therefore, here we present the results from a global 3D hybrid simulation using the AuburN Global hybrid CodE in 3D (ANGIE3D) hybrid code (Lin et al., 2014). The ANGIE3D code has been used in simulations of the solar wind‐magnetosphere coupling and global dynamics in the magnetosphere, including the magnetotail, magnetopause, and plasma sheet (Lin et al., 2014, 2017, 2021, 2022; Lu et al., 2016; Lu, Lin, et al., 2015; Lu, Lu, et al., 2015; Wang et al., 2020, 2021).…”
Section: Global Hybrid Simulationmentioning
confidence: 99%
“…We use the results from the ANGIE3D simulation runs that had been conducted previously for other investigations (some of the simulations have been published, e.g., Wang et al. (2020, 2021)). These simulations all have non‐zero IMF B y and magnitudes of the IMF components and solar wind parameters specified in these simulations are all within observed ranges, but they can be very different from one simulation to another, such as very different solar wind speeds, because they were designed for different focus targets.…”
Section: Global Hybrid Simulationmentioning
confidence: 99%